Identifikasi Miskonsepsi Siswa Menggunakan Tes Diagnostik Six Tier dengan CRI (Certainty of Response Index) pada Materi Gelombang - Auvi Winandri Utami; Siti Nurul Khotimah (Jurnal Penelitian Pendidikan IPA, 2023)
The concept of waves is essential in physics learning. This study aims to obtain a six-level diagnostic test instrument accompanied by a Certainty of Response Index (CRI) and use it to identify students' level of conceptual understanding and misconceptions on wave material. This study used the Research and Development (R&D) method with a sample of 220 students. Misconception data was obtained using a misconception test in the form of multiple-choice questions. There are 32 questions with six stages consisting of multiple choices answer, the level of confidence in choosing answers, the source of answer choices, the choice of reasons in answering questions, the level of confidence in selecting causes, and the source of students' reasons in answering the questions. The results showed that the percentage of students who experienced misconceptions in the whole question was 36%. Students who understood the concept was 30%, and 34% of students did not understand the concept. In addition, 61% of students chose answers and reasons for solutions based on personal opinions. The conclusion is that misconceptions are caused by student errors in applying the concepts received in the given problem, and students tend to choose the correct answers and reasons when the issue presented is equipped with a picture and only requires one step to get the correct answer.